The Influence of Physical Education on Adolescents' Motor and Psychological Development - Firayani, Firayani (PT. Anagata Sembagi Education, 2025)
Physical education plays an important role in supporting the motor and psychological development of adolescents. Optimal motor development not only improves physical abilities but also has a positive impact on psychological aspects such as self-confidence, motivation, and mental well-being. This study aims to analyze the effect of physical education on the motor and psychological development of adolescents through a qualitative approach. Data were obtained from in-depth interviews with physical education teachers, observations of physical education learning activities in secondary schools, and group discussions with students. The results of the study indicate that structured and continuous physical education can improve gross and fine motor skills while strengthening psychological aspects such as emotional control, self-confidence, and social skills of adolescents. Social interaction during physical activities strengthens relationships between friends and reduces stress. However, several obstacles such as lack of facilities and variety of learning materials are still challenges. This study recommends improving the quality of physical education by paying attention to the psychological and motor needs of adolescents through innovative learning methods and improving supporting facilities. Thus, physical education can contribute holistically to the development of healthy and productive adolescents.